Implementation of Cognitive Strategies in Teaching Expository Writing to Tenth-Grade Students at SMA IT Granada Samarinda - Agus Salim Razak (Journal of Social Research, 2025)
This study aims to describe the implementation steps and effectiveness of cognitive strategies in teaching expository writing to tenth-grade students at SMA IT Granada Samarinda. The research was motivated by low writing proficiency among students, particularly their difficulty in organizing ideas logically and coherently. Using a qualitative approach, data were collected through observation, documentation, and written tests involving 90 students across four classes. The cognitive strategies implemented included repetition, elaboration, information organization (mind mapping), and metacognition, which were integrated into five stages of the writing process: prewriting, drafting, revising, editing, and publishing. The findings indicate that cognitive strategies significantly assisted students in developing well-structured texts and constructing logical arguments. Class averages showed improvement with scores of 86 (X A1), 82 (X A2), 84 (X B1), and 80 (X B2), all exceeding the minimum competency standards. Moreover, these strategies enhanced student engagement and improved learning outcomes beyond expectations. The study concludes that cognitive strategies are effective in improving students' expository writing skills and are recommended for broader application in Indonesian language instruction.